NANO-GLASS-IONOMER CEMENTS IN MODERN RESTORATIVE DENTISTRY - Maya G. Lyapina; Mariana Tzekova; Maria Dencheva; Assya Krasteva; Mariela Yaneva-Deliverska; Angelina Kisselova (Peytchinski Publishing, 2016)
The incorporation of nanoparticles into glass powder of glass ionomers led to wider particle size distribution, which resulted in higher mechanical values. Consequently they can occupy the empty spaces between the Glass ionomer particles and act as reinforcing material in the composition of the glass ionomer cements. The nanofiller components of nano ionomers also enhance some physical properties of the hardened restorative. Its bonding mechanism should be attributed to micro-mechanical interlocking provided by the surface roughness, most likely combined with chemical interaction through its acrylic/itaconic acid copolymers. The paper reviews their secondary caries prevention - fluoride release properties, mechanical and physical propreties, biocompatibility aspects, and antimicrobial activity.